A NEW SPECIES OF COCCOPHAGUS FROM NUEVO LEON, MEXICO (HYMENOPTERA: CHALCIDOIDEA: APHELINIDAE) - Myartseva, S. N. (Instituto de Ecología, A.C., 2006)
A new species of aphelinids, from the state of Nuevo León, Mexico, Coccophagus gonzalezi sp.nov., is described and illustrated.